Pendeteksian dan Pencegahan Serangan Remote Command Execution Pada HTTP File Server dengan Menggunakan SNORT - Prasetyo, Yudhi, Fatah Yasin Al Irsyadi, S.T., M.T (2015)
Development of computer technology more facilitate user for kinds of information or data. Web application became place for sharing data activity about it. Educational institution and company also take a part on those advantages. The easy of this facility on sharing data worm out attacking that can be done by side variety. The attacking has a mean to get valuable data or just for interfering connectivity that using by another user. This research will discuss about how to detect an attacking remote command execution that to do toward sharing data media Rejetto HTTP File Server by using system attacking detection that formed snort and to do preventive by build active rule firewall. Rule snort will identify each of data into it and decide kinds of data which part from attacking remote command execution nor not. Result of this research is safety system of computer networking that capable on detect attacking of remote command execution which attack Rejetto HTTP. Server File and collaborate with firewall configuration manually that is used as preventive action, so those attack will not happen anymore.